68Ga-DOTATOC PET/CT to detect immune checkpoint inhibitor-related myocarditis - Joe-Elie Salem; Solange Peters; Olivier Michielin; Michel Obeid; Hasna Bouchaab; Javid J Moslehi; Sofiya Latifyan; Matthieu Perreau; John O Prior; Craig Fenwick; Sarah Boughdad; Madeleine Suffiotti; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitor (ICI)-related myocarditis is a rare but potentially fatal adverse event that can occur following ICI exposure. Early diagnosis and treatment are key to improve patient outcomes. Somatostatin receptor-based positron emission tomography–CT (PET/CT) showed promising results for the assessment of myocardial inflammation, yet information regarding its value for the diagnosis of ICI-related myocarditis, especially at the early stage, is limited. Thus, we investigated the value of 68Ga-DOTA(0)-Phe(1)-Tyr(3)-octreotide (68Ga-DOTATOC) PET/CT for the early detection and diagnosis of ICI-related myocarditis.Methods Consecutive patients with clinically suspected ICI-related myocarditis from July 2018 to February 2021 were retrospectively evaluated in this single-center study. All patients underwent imaging for the detection of ICI-related myocarditis using either cardiac magnetic resonance (CMR) imaging or 68Ga-DOTATOC PET/CT. PET/CT images were acquired 90 min after the injection of 2 MBq/kg 68Ga-DOTATOC with pathological myocardial uptake in the left ventricle (LV) suggestive of myocarditis defined using a myocardium-to-background ratio of peak standard uptake value to mean intracavitary LV standard uptake (MBRpeak) value above 1.6. Patients had a full cardiological work-up including ECG, echocardiography, serum cardiac troponin I (cTnI), cardiac troponin T and creatine kinase (CK), CK-MB. Endomyocardial biopsy and inflammatory cytokine markers were also analyzed. The detection rate of ICI-related myocarditis using 68Ga-DOTATOC PET/CT and CMR was assessed.Results A total of 11 patients had clinically suspected ICI-related myocarditis; 9 underwent 68Ga -DOTATOC PET/CT. All nine (100%) patients with 68Ga-DOTATOC PET/CT presented with pathological myocardial uptake in the LV that was suggestive of myocarditis (MBRpeak of 3.2±0.8, range 2.2–4.4). Eight patients had CMR imaging and 3/8 (38%) patients had lesions evocative of myocarditis. All PET-positive patients were previously treated with a high dose of steroids and intravenous immunoglobulin prior to PET/CT had elevated serum cTnI except for one patient for whom PET/CT was delayed several days. Interestingly, in 5/6 (83%) patients who presented with concomitant myositis, pathological uptake was seen on whole-body 68Ga-DOTATOC PET/CT images in the skeletal muscles, suggesting an additional advantage of this method to assess the full extent of the disease. In contrast, four patients with CMR imaging had negative findings despite having elevated serum cTnI levels (range 20.5–5896.1 ng/mL), thus defining possible myocarditis. Newly identified immune correlates could provide specific biomarkers for the diagnosis of ICI-related myocarditis. Most tested patients (six of seven patients) had serum increases in the inflammatory cytokine interleukin (IL)-6 and in the chemokines CXCL9, CXCL10, and CXCL13, and the mass cytometry phenotypes of immune cell populations in the blood also showed correlations with myocardial inflammation. Four of five patients with myocarditis exhibited a Th1/Th2 imbalance favoring a pronounced inflammatory Th1, Th1/Th17, and Th17 CD4 memory T-cell response. The high proportion of non-classical monocytes and significantly reduced levels of CD31 in four to five patients was also consistent with an inflammatory disease.Conclusion The use of 68Ga-DOTATOC PET/CT along with immune correlates is a highly sensitive method to detect ICI-related myocarditis especially in the early stage of myocardial inflammation, as patients with elevated cTnI may present normal CMR imaging results. 68Ga-DOTATOC PET/CT is also useful for detecting concomitant myositis. These results need to be confirmed in a larger population of patients and validated against a histological gold standard if available.